From political enemy to profane reality: the 'friend–enemy' relation in the political ideology of Italian communists. Issue 1 (1st January 2017) - Guiso, Andrea
Abstract: The 'friend–enemy' relation represented an essential ideological mainstay of the thought and action of the Italian Communist Party (PCI) in the years of republican Italy. This relation goes back to the aftermath of World War I when Soviet communism became established as a global revolutionary movement. The PCI's strategy of delegitimation of political opponents underwent substantial changes over the years of republican Italy. The long period spanning Togliatti and Berlinguer's leadership of the party saw a change in political culture destined to alter the very nature of the 'friend–enemy' relation. Particularly in the 1970s, with the so-called 'moral question', a new antiparty public discourse became established and was implemented mainly against the parties in government. This paved the way to a more radical and absolute logic of enmity that, in the long run, overwhelmed the PCI itself in the dramatic transition from First to Second Republic.